2010
DOI: 10.1016/s0828-282x(10)70398-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular burden and related risk factors among Nunavik (Quebec) Inuit: Insights from baseline findings in the circumpolar Inuit Health in Transition cohort study

Abstract: The current belief that the Inuit are protected from CVD is seriously questioned by the results of the present study. Considering the extremely high prevalence of CVD risk factors, a population-based intervention reinforced for women is urgently needed to reduce their risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 36 publications
0
46
0
Order By: Relevance
“…The existing literature is limited to a 2006 survey based on self-reported data that showed a 3% prevalence among adults aged 15 and older 12 and a 2004 survey of adults in Nunavik, Quebec, that showed a prevalence of 4.7% based on fasting glucose screening and medical chart reviews. 3 Our findings suggest that the prevalence of diabetes among Canadian Inuit is higher than previ-…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The existing literature is limited to a 2006 survey based on self-reported data that showed a 3% prevalence among adults aged 15 and older 12 and a 2004 survey of adults in Nunavik, Quebec, that showed a prevalence of 4.7% based on fasting glucose screening and medical chart reviews. 3 Our findings suggest that the prevalence of diabetes among Canadian Inuit is higher than previ-…”
Section: Discussionmentioning
confidence: 62%
“…[1][2][3] A high prevalence of obesity among Canadian Inuit has been noted, 3,4 and yet studies have suggested that the metabolic consequences of obesity may not be as severe among Inuit as they are in predominantly Caucasian or First Nations populations. [4][5][6] Conversely, the prevalence of type 2 diabetes mellitus, which was noted to be rare among Inuit in early studies, 7,8 now matches or exceeds that of predominately Caucasian comparison populations in Alaska and Greenland.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Food security is defined as when all people at all times have access to sufficient, safe, nutritious food to maintain a healthy and active life (World Food Summit, 1996); when this is not the case, a situation of food insecurity arises. Consequently, increasingly poor nutrition, combined with lifestyle changes such as reduced physical activity and elevated consumption of alcohol and cigarettes, are setting the stage for a major emergence of obesity and diet-sensitive chronic diseases, particularly among Inuit youth and women (Chateau-Degat et al, 2010;Egeland et al, 2011).…”
Section: Implications Of Study Results For the Broader Nunavik Publicmentioning
confidence: 99%
“…An individual was defined as having HTN (hypertension) if his/her BP was ≥140/90 mmHg (19) or if he/ she had a previous diagnosis of HTN with or without medication. Hypertension diagnosis was ascertained by individual medical file review as detailed elsewhere (20). The mean of pulse pressure was defined as the difference between systolic blood pressure (SBP) and diastolic blood pressure (DBP).…”
Section: Methodsmentioning
confidence: 99%